2023
DOI: 10.3126/ajms.v14i3.49860
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of drug-resistant tuberculosis (DR-TB) following uptake of universal drug susceptibility testing: A record review from a nodal DR-TB center

Abstract: Background: There has been delay evident in diagnosing the drug resistance and non-initiation of appropriate treatment based on drug susceptibility pattern resulting in poor treatment outcome of drug-resistant tuberculosis (DR-TB). Aims and Objectives: The aims of this study were to examine the treatment outcomes for DR-TB patients following universal drug susceptibility testing (UDST) and to examine the association of sociodemographic, behavioral factors, or comorbidities with outcome. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…21,31,37 Despite the massive TB burden, India is actively spending $23 billion a year to successfully reduce the global TB burden through the World Health Organization's End Tuberculosis Strategy and the Revised National Tuberculosis Control Program (RNTCP), as well as by establishing "Nikshay, " an open web service that allows health organizations and medical councils to more easily track antibiotic use in real time as part of the Direct Observed Treatment Service. [38][39][40] However, there are still a lot of gaps in the fight against TB because of a lack of information, a lack of awareness, a lot of myths and misconceptions, and the failure to pay fees to accredited social health activists (ASHA) workers. 3,5,35 According to the National Family Health Survey-5 (NFHS-5) and several research investigations, certain social determinants are found to have the highest prevalence of TB (Fig 3).…”
Section: Occurrences Of Tb In Indiamentioning
confidence: 99%
See 4 more Smart Citations
“…21,31,37 Despite the massive TB burden, India is actively spending $23 billion a year to successfully reduce the global TB burden through the World Health Organization's End Tuberculosis Strategy and the Revised National Tuberculosis Control Program (RNTCP), as well as by establishing "Nikshay, " an open web service that allows health organizations and medical councils to more easily track antibiotic use in real time as part of the Direct Observed Treatment Service. [38][39][40] However, there are still a lot of gaps in the fight against TB because of a lack of information, a lack of awareness, a lot of myths and misconceptions, and the failure to pay fees to accredited social health activists (ASHA) workers. 3,5,35 According to the National Family Health Survey-5 (NFHS-5) and several research investigations, certain social determinants are found to have the highest prevalence of TB (Fig 3).…”
Section: Occurrences Of Tb In Indiamentioning
confidence: 99%
“…5,29,31,37,41,42 Although it is evident that rural and urban slums areas have a comparatively greater TB incidence, the prevalence has decreased as people's socioeconomic position has improved. 31,[40][41][42][43][44]…”
Section: Occurrences Of Tb In Indiamentioning
confidence: 99%
See 3 more Smart Citations